Pengaruh Kelompok Referensi Dan Social Media Marketing Terhadap Keputusan Penggunaan Jasa Rawlins Laundry - Edwardo Hotman P.S; Ajat Sudrajat (Peneliti.net, 2022)
IThis study aims to find out the reference group and influential Social Media Marketing partially and simultaneously to the decision to use Rawlins laundry services and also to determine the correlation of reference group variables between social media marketing.The data collection methods used in this study are descriptive test, validity test, reliability test, normality test, correlation analysis, T test and F test. There was a partial positive and significant influence between the Reference Group on the Decision to Use services with a contribution of 0.207 or 20.7%., the sig value. 0.000 < α 0.10 and t count 5.841 > t table 1.66071 then Ho rejected .There was a partial positive and significant influence between Social Media Marketing on the Decision to Use Services with a contribution of 0.426 or 42.6%. sig value. 0.000 < α 0.10 and t count 5.841 > t table 1.66071 then Ho rejected.The correlation of reference groups between social media marketing was 0.762.There was a simultaneous positive and significant influence between the Reference Group and Social Media Marketing on the Decision to Use Services on Rawlins laundry with a contribution of 0.657 or 65.7% and 34.3% can be explained by other variables that were not studied in this study.